Cardiac muscle apoptosis: a comparison of myocardium revascularization with and without cardiopulmonary bypass - Gaia,Diego Felipe (2003)
OBJECTIVE: Inflammatory response and metabolic disturbances in coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB) and without (OFF-PUMP) have been researched. Apoptosis in ischemic reperfusion and chronic disease models has been shown in recent studies. The objective of this study is to compare the apoptosis intensity detected in cardiac myocytes before and after CABG with and without cardiopulmonary bypass. METHOD: Eighteen patients undergoing elective CABG were divided in two groups: the first group underwent cardiopulmonary bypasses and the second group did not. Auricle myocardial samples were obtained at the beginning and at the end of the surgery. Specimens were examined for apoptosis using the TUNEL method. RESULTS: There was no significant difference between the two groups in the surgical, demographic and postoperative data. The number of grafts was statistically different. There was no significant difference between the numbers of cells undergoing apoptosis in the two groups at the beginning of the procedure. There was no significant difference in the number of cells undergoing apoptosis from the beginning to the end of CABG in the OFF-PUMP group. There was a significant difference between the number of cells undergoing apoptosis at the beginning and the end of the CABG in the CPB group (p<0.01). CONCLUSION: The smaller number of cells undergoing apoptosis in the OFF-PUMP group is in accordance with published data that suggest CPB is capable of promoting cell lesion. Having shown that, another favorable argument can be added to the indication of the CABG without CPB.